Laminin 332 expression levels predict clinical outcomes and chemotherapy response in patients with pancreatic adenocarcinoma - Sari, Bilge; Gulbey, Ozcan; Hamill, Kevin J. (Frontiers in Cell and Developmental Biology, 2023)
Poor outcomes and chemotherapy resistance for patients with pancreatic adenocarcinoma (PAAD) are a challenge worldwide, and new or improved prognostic biomarkers are urgently required. Individual laminin family members have been established as cancer-associated markers, predicting patient outcomes in many cancer types, including PAAD. Here, we used multiple modalities including RNAseq and gene chip, and genomic and proteomic data to examine the relationships of all laminin genes in PAAD with clinical outcomes. These analyses identified that LAMA3, LAMB3 and LAMC2 expression levels are increased at the mRNA and protein levels in PAAD tumours with evidence of co-regulation. Increased expression of all three genes was associated with decreased promoter methylation status, TP53 mutations, and altered receptor tyrosine kinase (RTK) pathways. Clinically, high LAMA3, LAMB3 and LAMC2 transcript abundance were each related to advanced histological grade. Moreover, high expression of these genes individually predicted poor patient survival, while a signature of combined high expression of LAMA3, LAMB3 and LAMC2 was a stronger predictor of patient outcomes than each gene alone. Interestingly, cell lines with high expression of LM332 chains were not sensitive to the commonly used PAAD chemotherapy drugs Paclitaxel and Gemcitabine; however, increased sensitivity was evident for Erlotinib, Afatinib, Gefinitib and Cetuximab Epidermal Growth Factor (EGFR) RTK inhibitors. To explore possible mechanisms, we investigated co-expressed genes, identifying eight hub genes; GJB3, ITGB6, SERPINB5, GPRC5A, PLEK2, TMPRSS4, P2RY2, and TRIM29, which are co-expressed with all three of LAMA3, LAMB3 and LAMC2. Of these, only SERPINB5 provided a stronger predictive value than the laminin-encoding genes. Together these multiple integrated analyses suggest that the combined expression of LM332 is a useful prognostic biomarker for PAAD and could help patient stratification and therapeutic selection.